An assessment of the overexpression of BMP-2 in transfected human osteoblast cells stimulated by mineral trioxide aggregate and Biodentine - Rodrigues, E. M. [UNESP]; Gomes-Cornelio, A. L. [UNESP]; Soares-Costa, A.; Salles, L. P.; Velayutham, M. [UNESP]; Rossa-Junior, C. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley-Blackwell, 2017)
AimTo evaluate the effect of MTA and Biodentine on viability, osteogenic differentiation and BMP-2 expression in osteogenic cells. MethodologySaos-2 cells were used as a model of osteoblastic cells. Overexpression of BMP-2 was induced by transfection of a CMV-driven plasmid construct including the human BMP-2 coding sequence, and stably transfected cells were selected. Cell viability was assessed by the mitochondrial dehydrogenase enzymatic (MTT) assay. The bioactivity of the materials was evaluated by the alkaline phosphatase (ALP) assay and detection of calcium deposits with alizarin red staining (ARS). The gene expression of BMP-2 and ALP was quantified with real-time PCR. Statistical analysis was performed with analysis of variance and Bonferroni or Tukey post-test (=0.05). ResultsViability tests revealed that MTA and Biodentine were not cytotoxic at the higher dilution (1:8) to BMP-2-transfected cells. MTA and Biodentine exhibited the highest ALP activity when compared to the Saos-BMP-2-unexposed control group (P<0.05). Cell exposure to Biodentine and MTA had a significant stimulatory effect on the formation of mineralized nodules (P<0.05). The highest increase in BMP-2 gene expression was observed after 3days of BMP-2-transfected cells exposure to MTA and Biodentine in non-osteogenic medium in relation to Saos-BMP-2-unexposed control cells (P<0.05). Exposure of cells to MTA in osteogenic medium for 1day increased ALP gene expression by approximately 1.3-fold in relation to Saos-BMP-2-unexposed control cells (P<0.05). ConclusionsBoth MTA and Biodentine showed biocompatibility and bioactivity in Saos-BMP-2 overexpressing cells. Biodentine had a significantly greater effect on mineralization than MTA. Both MTA and Biodentine enhanced BMP-2 mRNA expression in the transfected system. Both MTA and Biodentine are suitable materials to improve osteoblastic cell mineralization.
Keywords: bioactivity; Biodentine; bone morphogenetic protein-2; cytotoxicity; MTA